Artistic and figurative statements in Ukrainian scenography of the XX century - T. K. Ognieva (Ukrainian Cultural Studies, 2021)
The article "Artistic and figurative statements in the Ukrainian scenography of the XX century" analyzes the conditions and factors of development of the art of theater and scenography as a component during the XX century in Ukraine. The scenographic space provides an opportunity to synthesize elements of plastic arts to create an artistic and figurative solution and to form the emotional climate of a theatrical performance. During the development of the art of theater, an evolution of the scenography took place. The level of scenography in Ukraine in the 1920s and 1930s not only corresponded to the standards of the world art, but also exceeded its value orientations, provided the key to understanding artistic searches and discoveries on a global scale. Ukrainian scenographers offered independent artistic and figurative solutions of performances. In the scenography of the 1920s, O. Khvostenko-Khvostov used various means of design of space – construction, painting, fabrics, mobile machine, banner, film projection, light, photomontage, etc. A. Petritskyi even managed to give constructivism diversity and emotionality, perfectly synthesize the spatio-temporal characteristics of theatrical art, forming an artistic and figurative solution of the play. W. Meller’s work in the 20s-30s of the XXth century is also an example of artistic figurative stage design of the play and the most fruitful interpretation of European innovative trends on the basis of Ukrainian theatrical art. The "social realism" style approved by the influenced the development of Ukrainian culture; in theatrical art and, in particular, scenography, we observe a gradual departure from the artistic and figurative organization of the stage towards realistic reproduction of the place of action. Thus, the legacy of V. Meller, A. Petritskyi and O. Khvostenko-Khvostov before and after World War II is not distinguished by innovative, extraordinary stage solutions, which is explained by objective reasons. D. Borovskyi was one of the first scenographers of the post – war period who demonstrated artistic and figurative interpretation of dramatic material in Ukraine. Myron Kyprian has a special place among the artists of the stage, whose creative work of the 60s – 70s of the XX century abounds in artistic and figurative solutions of performances. We emphasize that the Ukrainian scenography in the 50’s – 60’s generally corresponded to the basic principles of the style of socialist realism. Most artists of the stage used standard techniques, but there were also artistic and figurative scenographic solutions that stood out from the general usual practice. The process of liberation of art in general and theatrical in particular has shifted and is constantly evolving towards getting rid of the dictates of worldview principles and aesthetic systems that determined the ways of development of art in previous years. The solution of the problems of visualization of the artistic and figurative organization of the stage space is the principle of universalism of the stage environment, plastic embodiment of ideas. At the end of the XXth century artists turned to a variety of artistic techniques in an effort to embody the symbolic subtext and philosophical content of the dramatic material by enriching the palette of expressive and technical means. The scenography system combines various elements, visual and plastic characteristics of materials to metaphorize the action. The large-scale, monumental plastic embodiment of the main idea of the artist – scenographer coexists with the empty space of the stage. At the end of the twentieth century we observe the mutual enrichment and spiritual growth of artists – scenographers who form the artistic and figurative solution of the play and the audience, able to perceive and care about the metaphorical symbolic sphere of plastic – spatial coordinates of the play.